Harmonisasi Sistem Litigasi Elektronik Dan Non-Litigasi Dalam Penyelesaian Sengketa Bisnis Digital - Mukhidin, Mukhidin; Kus Rizkianto; Pratama, Erwin Aditya (Universitas Pancasakti Tegal, 2025)
The development of digital technology has brought significant transformation to business practices while simultaneously generating new potential disputes that require adaptive resolution mechanisms. In Indonesia, the emergence of the electronic litigation system (e-court) offers a formal court-based solution, while non-litigation mechanisms based on Online Dispute Resolution (ODR) provide a more flexible, fast, and efficient alternative. However, these two mechanisms still operate partially without a clear integration framework, raising questions about the effectiveness of digital business dispute resolution. This article addresses two research problems: (1) how the development and implementation of e-court and ODR in resolving digital business disputes in Indonesia have evolved, and (2) what harmonization model can be established to create a more comprehensive, efficient, and just dispute resolution mechanism. The findings show that e-court has provided legal certainty and formal legitimacy but remains limited to time-consuming litigation processes. Conversely, ODR meets the needs of efficiency and speed but faces challenges in regulation and the acceptability of decisions. The discussion highlights the importance of a harmonization model that integrates the strengths of e-court in terms of legal formality with the flexibility of ODR in non-litigation processes. Harmonization can be pursued through the establishment of regulations recognizing ODR as part of the judicial system, strengthening digital infrastructure, and enhancing legal literacy among disputing parties. Thus, harmonizing these two mechanisms is expected to address the challenges of digital business dispute resolution in the era of technological transformation.